Activity-associated effect of LDL receptor missense variants located in the cysteine-rich repeats. Issue 2 (February 2015) - Etxebarria, A.; Benito-Vicente, A.; Stef, M.; Ostolaza, H.; Palacios, L.; Martin, C.
Abstract: Background : The LDL receptor (LDLR) is a Class I transmembrane protein critical for the clearance of cholesterol-containing lipoprotein particles. The N-terminal domain of the LDLR harbours the ligand-binding domain consisting of seven cysteine-rich repeats of approximately 40 amino acids each. Mutations in the LDLR binding domain may result in loss of receptor activity leading to familial hypercholesterolemia (FH). In this study the activity of six mutations located in the cysteine-rich repeats of the LDLR has been investigated. Methods : CHO- ldlA7 transfected cells with six different LDLR mutations have been used to analyse in vitro LDLR expression, lipoprotein binding and uptake. Immunoblotting of cell extracts, flow cytometry and confocal microscopy have been performed to determine the effects of these mutations. In silico analysis was also performed to predict the mutation effect. Results and conclusion : From the six mutations, p.Arg257Trp turned out to be a non-pathogenic LDLR variant whereas p.Cys116Arg, p.Asp168Asn, p.Asp172Asn, p.Arg300Gly and p.Asp301Gly were classified as binding-defective LDLR variants whose effect is not as severe as null allele mutations. Highlights: Activity of six variants within LDLR ligand binding domain has been studied. p.Arg257Trp turned out to be a non pathogenic LDLR variant. p.Cys116Arg, p.Asp168Asn, p.Asp172Asn, p.Arg300Gly and p.Asp301Gly are Class 3 LDLR. VLDL binding activity has been used to determine structural changes in the modules. Knowledge of the pathogenicity of these variants helps to interpret FH genetic diagnosis.